The Use of Mask in Respiratory Exercise in the Era of COVID-19 Pandemic - Susanthy Djajalaksana; Aditya Sri Listyoko; Lucky Togihon Harjantho; Anthony Christanto; Silvy Amalia Falyani; Akira Yamasaki (Jurnal Respirasi, 2022)
Introduction: The 2019 Coronavirus Disease (COVID-19) pandemic causes public health protocols to be strictly enforced. This study examined the effect of using masks on performing exercises, particularly respiratory exercises, in the era of COVID-19 pandemic. Methods: A total of 24 people participated in this study using randomization and cross-over techniques. The variables measured were respiratory rate, oxygen (O2) saturation, pulse rate, carbon monoxide (CO) levels, and fatigue scale using the Borg Breathless Score. The statistical test used independent t-test, Wilcoxon, and Mann-Whitney U with a different level of p < 0.05. Results: There was no significant difference between the observed parameters (heart rate, respiratory rate, peripheral O2 saturation, CO levels, and Borg scale) in the groups using masks and not using masks. Conclusion: The increase in pulse rate, respiratory rate, and Borg Scale in the aerobic phase of respiratory exercise is physiological and can improve significantly after the cooling phase.